Successful research supervision advising students doing research - Lee, Anne (Routledge, 2020)
"The new and fully updated second edition of Successful Research Supervision offers a research-based practical framework for academics to examine and develop their effectiveness as research supervisors. By identify the optimum combination of approaches to best fit individuals this text helps supervisors to move their students towards the ultimate goal of being able to study independently in a thoughtful, coherent and efficient manner. This go-to guide for both novice and experienced supervisors takes the reader from the initial steps, to managing a project through to successful completion. Successful Research Supervision is crucial reading to all those seeking to develop their practice"--Provided by publisher.